A scoping review of end-of-life discussions and palliative care: implications for neurological intensive care among Latinos in the U.S. - Monica M. Diaz; Lesley A. Guareña; Bettsie Garcia; Christoper A. Alarcón-Ruiz; Stella Seal; Clio Rubiños; Dulce M. Cruz‐Oliver; J. Ricardo Carhuapoma (My University, 2024)
Goals of care (Goals-of-care) discussions and palliative care (PC) are crucial to providing comprehensive healthcare, particularly for acute neurological conditions requiring admission to a neurological intensive care unit. We identified gaps in the literature and describe insight for future research on end-of-life discussions and PC for U.S. Latinos with acute neurological conditions. We searched 10 databases including peer-reviewed abstracts and manuscripts of hospitalized U.S. Latinos with acute neurological and non-neurological conditions. We included 44 of 3231 publications and identified various themes: PC utilization, pre-established advanced directives in Goals-of-care discussions, Goals-of-care discussion outcomes, tracheostomy or percutaneous gastrostomy tube placement rates among hospitalized Latinos. Our review highlights that Latinos appear to have lower palliative care utilization compared with non-Latino Whites and may be less likely to have pre-established advanced directives, more likely to have gastrostomy or tracheostomy placement and less likely to have do-not-resuscitate status.
Keywords: Palliative care; Medicine; Gastrostomy tube; Intensive care unit; Percutaneous endoscopic gastrostomy; Gastrostomy; Acute care; Do not resuscitate; End-of-life care; Nursing; MEDLINE; Intensive care; Intensive care medicine; Health care; Finance; Economics; PEG ratio; Political science; Law; Surgery; Economic growth; Palliative care; Medicine; Gastrostomy tube; Intensive care unit; Percutaneous endoscopic gastrostomy; Gastrostomy; Acute care; Do not resuscitate; End-of-life care; Nursing; MEDLINE; Intensive care; Intensive care medicine; Health care; Health Sciences Medicine Public Health, Environmental and Occupational Health Palliative Care and End-of-Life Issues; Social Sciences Psychology Clinical Psychology Healthcare Decision-Making and Restraints; Health Sciences Health Professions Radiological and Ultrasound Technology Family and Patient Care in Intensive Care Units